On Classical Liberalism and Libertarianism - Barry, Norman. author. aut Link
XI, 215 p.
Keywords: This first systematic analysis of the full range of classical liberal thinking covers the utilitarianism of Hume, Smith and their successors, the Austrian and Chicago schools of political economy, 'contractarian' liberalism and the ethical individualism of Ayn Rand and Robert Nozick. Norman Barry also discusses the hitherto barely understood theory of anarcho-capitalism and throughout his analysis draws attention to the differences in fundamental philosophical outlook that underline superficially similar policy positions.